Microstructures, mechanical properties and degradability of Mg-2Gd-0.5(Cu/Ni) alloys: A comparison study. (20th November 2022) - Zhong, Shiyu; Zhang, Dingfei; Wang, Yongqin; Chai, Sensen; Feng, Jingkai; Luo, Yulun; Hua, Jianrong; Dai, Qimin; Hu, Guangshan; Xu, Junyao; Jiang, Bin; Pan, Fusheng
Highlights: The addition of minor Ni (0.25 and 0.5 wt.%) promoted the formation of LPSO phases. Adding Ni was more effective in strengthening basal fiber texture than adding Cu. Adding Ni was more effective in refining grain sizes than adding Cu. Adding Ni further increased the corrosion rate and strength than adding Cu. Adding Ni was more detrimental to work hardening and ductility than adding Cu. Abstract: Low alloying Mg-2Gd-0.5(Cu/Ni) alloys for sealing tools in the oil and gas industry were prepared. The differences in the effects of minor Cu and Ni additions on microstructures and properties of the Mg-2Gd alloy were compared. The results showed that adding Ni was more effective than adding Cu in refining grain sizes, strengthening the basal fiber texture, and promoting the formation of LPSO phases, resulting in higher strength. The tensile yield strength/elongation of the Mg-2Gd-0.5Cu alloy, Mg-2Gd-0.25Cu-0.25Ni alloy, and Mg-2Gd-0.5Ni alloy was 146 MPa/23.7%, 175 MPa/23.1%, and 248 MPa/18.2%, respectively. The decreased elongation was attributed to the basal fiber texture and the presence of coarse LPSO phases. In terms of the corrosion rate in 3.5 wt.% NaCl solution, it rose from 112 mm y –1 for the Mg-2Gd-0.5Cu alloy to 269 mm y –1 for the Mg-2Gd-0.25Cu-0.25Ni alloy and 490 mm y –1 for the Mg-2Gd-0.5Ni alloy, indicating that the addition of Ni instead of Cu showed a more significant promoting effect on the degradability of Mg alloys, which was related to more refined grains, the stronger basal fiber texture, and a larger amount of LPSO phases. Graphical abstract: Image, graphical abstract